PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI MASA PANDEMI COVID-19 DI SMP NEGERI 37 SAMARINDA - Nindya Angi Gayo; Ach. Faisol; Moh. Eko Nasrullah (VICRATINA, 2021)
What are the problems of learning Islamic religious education during the Covid-19 pandemic at SMP Negeri 37 Samarinda. How to overcome the problems of learning Islamic religious education during the Covid-19 pandemic at SMP Negeri 37 Samarinda. The research is a qualitative research and the type of research is a case study with the place of research at SMP Negeri 37 Samarinda. Data collection was carried out, among others, by using the method of observation, interviews, and documentation methods. Data analysis is done by summarizing important data and then draiwing conclusions. To test the validity of the data, in – depth intervies, longer observations, and triangulation were carried out.  Based on the results of the study, it shows that (1) The problems that exist in learning Islamic religious education do not only lie in the school environment but the less than optimal role of family in the implementation of Islamic religious education learning is also an obstacle in  learning Islamic religious education in junior high schools Negeri 37 Samarinda, (2) The solution, in addition to creating a conducive learning environment and trying to complete the media needed in the learning process, the school collaborates with parents to be more attentive and to be a good role model for their students.